Simulasi Gelombang Elektromagnetik Pada Waveguide Menggunakan Metode Finite Difference Time Domain Untuk Aplikasi Radar - Teguh Puja Negara; Erniyati Erniyati; Agus Ismangil (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
Electromagnetic wave simulation on waveguide has been carried out using the FDTD method. The electric field is reflected when it hits the dielectric rod and is transmitted over the canal. for metal rods, the electric field is blocked on the rod and dominant over the canal. The energy density transmitted at the end of the computational domain has been calculated and has different values according to the material used on the rod. These results can be applied to radar to detect objects using waves.